Organocatalytic acetylation of starch: Effect of reaction conditions on DS and characterisation of esterified granules - Tupa Valencia, Maribel Victoria (2015)
Starch acetates with varying degree of substitution (DS) were prepared by a novel solvent-free organocatalytic methodology. The acetylation protocol involved a non-toxic biobased α-hydroxycarboxylic acid as catalyst, and proceeded with high efficiency in absence of solvents. The effect of reaction conditions including reaction temperature (90-140 °C), catalyst load (0-2.3 g/g starch), acetic anhydride/starch weight ratio (6.5-13.5 g/g), and starch moisture content (0.6-14.8%) on the DS of the esters was evaluated. The analysis performed showed that the increase of temperature and catalyst concentration resulted in higher DS values, and evidenced a beneficial contribution of native starch moisture content on the substitution level achieved. Variation of reaction conditions allowed starch esters to be obtained with DS in the 0.03-2.93 range. Starch esters were characterised in terms of morphology, chemical structure, thermal properties, and distribution in polar/non polar liquid systems.